First principles study of structural, magnetic and electronic properties of CrAs. Issue 34 (2nd December 2017) - Autieri, Carmine; Noce, Canio
Abstract: We report ab initio density functional calculations of the structural and magnetic properties, and the electronic structure of CrAs. To simulate the observed pressure-driven experimental results, we perform our analysis for different volumes of the unit cell, showing that the structural, magnetic and electronic properties strongly depend on the size of the cell. We find that the calculated quantities are in good agreement with the experimental data, and we review our results in terms of the observed superconductivity.